Analysis of Water and Sediment Variation Characteristics in Jingjiang River Reach before and after Operation of Three Gorges Reservoir Based on GAM - DING Jiawei; PENG Yuming; CHEN Yanfei; SHEN Jian; HUANG Lieming (Renmin Zhujiang)
In order to explore the different water and sediment variation characteristics in Jingjiang River reach before and after the operation of the Three Gorges Reservoir, the Mann-Kendall trend test method and rescaled range (R/S) analysis method were used to analyze and predict the variation trend of water and sediment in Jingjiang River reach, and the generalized additive model (GAM) was constructed to quantitatively analyze the influence of water and sediment outflows from the Three Gorges Reservoir on the Jingjiang River reach. The results show that: After the operation of the Three Gorges Reservoir, the average annual sediment concentration in Jingjiang River reach has decreased significantly and will continue to decrease in the next 10 years, while the average annual discharge has changed little. The distribution of water and sediment is extremely uneven throughout the year, with peaks all occurring in July. The water and sediment outflows from the Three Gorges Reservoir have a significant non-linear effect on the sediment concentration in Jingjiang River reach but a linear effect on the discharge. The water and sediment outflows from the Three Gorges Reservoir have a significant impact on the water and sediment in Jingjiang River reach. The sediment runoff from the Three Gorges Reservoir contributes to 90% of the sediment concentration in Jingjiang River reach, and the outflow discharge from the Three Gorges Reservoir contributes to 99% of the discharge in Jingjiang River reach. When the amount of water and sediment outflows from the Three Gorges Reservoir is in different intervals, the sediment concentration in Jingjiang River reach presents different variation characteristics. In general, when the amount of water and sediment outflows from the Three Gorges Reservoir is at moderate to low levels, its influence on sediment concentration in Jingjiang River reach is more pronounced. This paper uses the GAM to quantitatively analyze the water and sediment variation characteristics in Jingjiang River reach before and after the operation of the Three Gorges Reservoir, which provides a scientific basis for the study and management of the water and sediment in Jingjiang River reach.